Development and validation of public–private partnerships framework for delivering housing projects in developing countries: a case of Tanzania. Issue 5 (15th April 2022) - Kavishe, Neema; Chileshe, Nicholas
Abstract: The supply of adequate houses is still a big challenge in many developing countries, particularly in Africa, where the population and urbanization rate is continuously growing. Increasingly Governments in many developing countries have adopted public–private partnerships (PPPs) to meet their housing needs. However despite the adoption, problems still remain and the progress is slow. Various studies have examined the ranges of issues that have produced the poor results in delivering PPP projects in developing countries. However; no tool (framework) has been developed to address these challenges for a successful outcome. Therefore, the aim of this study was to present a validated PPP framework which will address the identified challenges in order to improve housing delivery. The proposed housing PPP framework was empirically validated by 12 PPP experts who were purposely selected in order to ascertain its applicability, effectiveness and adaptability. The results of the validation showed that the proposed measures within the housing PPP (HPPP) framework all rated above the test value, thus demonstrating its viability. The implication of the findings is the applicability of the HPPP framework in assisting the stakeholders address the existing challenges. Second, the framework has the potential of providing valuable guidance and roadmaps for successful delivery of PPP housing projects in developing countries.